2021
DOI: 10.1002/1878-0261.13065
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in blood act as biomarkers of colorectal cancer and indicate potential therapeutic targets

Abstract: Association studies have linked alterations of blood‐derived microRNAs (miRNAs) with colorectal cancer (CRC). Here, we performed a microarray‐based comparison of the profiles of 2549 miRNAs in 80 blood samples from healthy donors and patients with colorectal adenomas, colorectal diverticulitis and CRC at different stages. Confirmation by quantitative real‐time PCR (RT‐PCR) was complemented by validation of identified molecules in another 36 blood samples. No variations in miRNA levels were observed in samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Over the years, we have studied the miR-content in cancer tissues and blood samples for both understanding tumor biology and determining the diagnostic potential [ 8 , 9 , 10 , 11 ]. miRs are non-protein-encoding RNA molecules that play a critical role in the post-transcriptional regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, we have studied the miR-content in cancer tissues and blood samples for both understanding tumor biology and determining the diagnostic potential [ 8 , 9 , 10 , 11 ]. miRs are non-protein-encoding RNA molecules that play a critical role in the post-transcriptional regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that miRNAs may play an important role in tumorigenesis and tumor progression. Thus, since then, an increasing number of studies have demonstrated that the aberrant expression of miRNAs is associated with cancer progression, including CRC ( 40 42 ).…”
Section: Introductionmentioning
confidence: 99%